BoLA - DRB3 Gene Polymorphism and its Association with Lactation Yield and Milk Constituents in Crossbred Cattle - Tayeng, Kauvery; Tomar, Satyendra Singh; Nanavat, Sandeep; Aich, Ranjit; Ignetious, Shely; Nagoriya, Sunil Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was undertaken to explore polymorphism at exon 2 of BoLA-DRB3 gene locus and its association with milk yield, fat % and protein % in a total of 40 Holstein-Friesian crosssbred cows using PCR-RFLP method. PCR-RFLP using Hae III restriction enzyme revealed presence of 7 genotypes with frequencies 0.475 (AA), 0.225 (AB), 0.050 (AE), 0.100 (BB), 0.050 (DD), 0.050 (EE) and 0.050 (II), respectively and PCR-RFLP using Bst YI yielded 3 genotypes with frequencies 0.050 (AA), 0.625 (AB) and 0.325 (BB), respectively. To study the association of BoLA-DRB3.2 genotypes with milk yield, fat and protein %, the data was subjected to analysis of variance employing general linear model using SPSS software package. Effect of farm (p <0.01) and parity (p <0.05) was significant on lactation yield; while the effect of season of calving, Hae III genotypes and Bst YI genotypes were non-significant. For fat % the effect of parity and season of calving was significant (p <0.05), while the effect of farm and genotype was non-significant. Milk protein % was significantly (p <0.05) influenced only by Bst YI genotype. Genotype AB recorded significantly higher protein % as compared to genotype BB.